PAI Teacher's Perspective on Educational Democracy in Elementary School 200515 Padangsidimpuan - Hasibuan, Kholidah Hannum; Nasution, Anhar (Cognoscere: Jurnal Komunikasi dan Media Pendidikan, 2024)
The purpose of this article is to examine how is the PAI teachers’ perspective on Educational Democracy. Where this article used qualitative as an approach. Education as a right for all mankind, is seen as a unifier in social life. Education is not only a way to become a better individual, but also seen as an increase in a person's status. In this case, it becomes an interesting discussion related to educational democracy which views education as being for everyone without siding with one group only. Educational democracy is also in line with Islamic views. This is an important study on how to implement educational democracy from the perspective of teachers, especially Islamic Religious Education teachers in schools. A teacher's perspective on equitable education is a benchmark for the success of educational democracy in schools. This article presents interviews with two Islamic Religious Education teachers at elementary school 200515 Padangsidimpuan as a form of their perspective on educational democracy and also observations as a form of deepening information about educational democracy in schools.